MASKULINITAS TOKOH UTAMA DALAM KUMPULAN CERITA PENDEK NADIRA KARYA LEILA S. CHUDORI - Dewi Purnama Sari; Chairil Effendy; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe background of this research was about masculinity in the main character include form, that is all the nature, behavior, speech, and the mindset that shows the existence of masculinity, and the cause, that is everything that affects the emergence of masculinity on the main character. Theories used in this research are gender theory, form of masculinity, psychoanalysis, social learning, cognitive development, and gender scheme. The research method is descriptive with qualitative research form. The approach that used is sociology approach with the object of study in the form of social phenomena in literary works. The results of analysis about the form of masculinity include several things. Physical aspect, is no matter on appearance. Economic aspect, is the breadwinner and economic independence. Sexual aspect, is aggressive and single status is accepted. Psychology aspect, is rational and intellectual ability. Sociological aspect, is dominating, trusting, determining, admired by others, violence, and enjoying a free life. Personal aspect, is bold, quiet, discipline, independent, individualistic, showing no weakness, and being able to take risk. The causes of masculinity include family, peers, educational institutions (schools), and mass media. Keyword: character, gender, masculinity